Multi-level determinants of tele-healthcare: a case study in Italy. (2017) - Rosis, Sabina De; Barsanti, Sara
The routine deployment of tele-healthcare solutions in healthcare systems and at the system-level is challenging and often problematic. This article reports the results of a case study in Tuscany (Italy), aimed at investigating the factors that may affect these processes. A multi-level and multi-stakeholder sample of 32 informants were interviewed in-depth about topics based on a previous literature analysis. Crucial determinant factors in the management of tele-healthcare services were identified in relation to technological, individual, organisational and contextual aspects. A reorganisation of healthcare in line with more participatory dynamics of teamwork, and more collaborative relationships within and among healthcare organisations, as well as with other stakeholders could contribute to integrate tele-healthcare into practice. Leadership and a strategic vision could also strongly influence the implementation and deployment of tele-healthcare.